The Epigenomics of Schizophrenia, in the Mouse - Javidfar, Behnam (Am J Med Genet B Neuropsychiatr Genet, 2017)
Large-scale consortia including the Psychiatric Genomics Consortium, the Common Minds Consortium, BrainSeq and PsychENCODE, and many other studies taken together provide increasingly detailed insights into the genetic and epigenetic risk architectures of schizophrenia and offer vast amounts of molecular information, but with largely unexplored therapeutic potential. Here we discuss how epigenomic studies in human brain could guide animal work to test the impact of disease-associated alterations in chromatin structure and function on cognition and behavior. For example, transcription factors such as MYOCYTE-SPECIFIC ENHANCER FACTOR (MEF2C), or multiple regulators of the open chromatin mark, methyl-histone H3-lysine 4, are associated with the genetic risk architectures of common psychiatric disease and alterations in chromatin structure and function in diseased brain tissue. Importantly, these molecules also affect cognition and behavior in genetically engineered mice, including virus-mediated expression changes in prefrontal cortex and other key nodes in the circuitry underlying psychosis. Therefore, preclinical and small laboratory animal work could target genomic sequences affected by chromatin alterations in schizophrenia. To this end, in vivo editing of enhancer and other regulatory non-coding DNA by RNA-guided nucleases including CRISPR-Cas, and designer transcription factors, could be expected to deliver pipelines for novel therapeutic approaches aimed at improving cognitive dysfunction and other core symptoms of schizophrenia.